2021
DOI: 10.3390/pr9040639
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Fluidized Bed Hydrodynamics and Transport Phenomena—Progress and Understanding

Abstract: Fluidization technology has found widespread applications for a variety of chemical and physical transformations since its introduction in the first half of the 1900s [...]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The fluidized bed apparatus was proposed as an alternative roasting technique for its energy efficiency and low‐footprint synthesis (Di Renzo et al, 2021). In our previous study (Peña‐Correa et al, 2022), we compared fluidized bed roasting versus forced‐convective oven roasting by means of kinetics of formation of volatile organic compounds and effective water diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…The fluidized bed apparatus was proposed as an alternative roasting technique for its energy efficiency and low‐footprint synthesis (Di Renzo et al, 2021). In our previous study (Peña‐Correa et al, 2022), we compared fluidized bed roasting versus forced‐convective oven roasting by means of kinetics of formation of volatile organic compounds and effective water diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Inside the fluidized bed's chamber, the particles are highly mobile, resulting in relatively uniform bed temperatures. Consequently, dead zones, hot spots, inhomogeneities, and variability in the quality of the products are significantly mitigated, if not completely avoided (Di Renzo, Scala, & Heinrich, 2021). Moreover, sustainable energy production/conversion and low-footprint syntheses also occur (Di Renzo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, dead zones, hot spots, inhomogeneities, and variability in the quality of the products are significantly mitigated, if not completely avoided (Di Renzo, Scala, & Heinrich, 2021). Moreover, sustainable energy production/conversion and low-footprint syntheses also occur (Di Renzo et al, 2021). Even though the fluidized bed technique was introduced in the first half of the 1900s, there is no any published report on its use with cocoa beans.…”
Section: Introductionmentioning
confidence: 99%
“…21 This technique involves almost 100% convective heat transfer and is recognized for its low-carbon footprint. 22 In contrast, oven roasting is mainly based on conductive heat transfer from the metallic surface of the trays, thus resembling the traditional cocoa roasting. In our previous studies, 4,23 we found that the heat transfer efficiency of fluidized bed roasting reduced the roasting time by a factor of 12 compared to traditional roasting.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The technique is based on blowing a strong flow of hot air from the bottom of the roasting chamber, thus making the solid particles to constantly move, resembling a stirring fluid . This technique involves almost 100% convective heat transfer and is recognized for its low-carbon footprint . In contrast, oven roasting is mainly based on conductive heat transfer from the metallic surface of the trays, thus resembling the traditional cocoa roasting.…”
Section: Introductionmentioning
confidence: 99%